PENGARUH EDUKASI KESEHATAN BERBASIS VIDEO TERHADAP PENGETAHUAN DAN SIKAP PENCEGAHAN ANEMIA PADA REMAJA PUTRI DI SMK-N 4 PALANGKA RAYA - Riani, Pella; Sukriani, Wahidah; Lucin, Yeni (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Adolescence is a period that is vulnerable to anemia. According to WHO, the prevalence of anemia among young women in developing countries is still high at around 53.7%. Currently, TikTok is a new trend among teenagers, so it can be used as an information medium to convey information about anemia in adolescents. The purpose of this study was to determine the effect of TikTok video-based health education on knowledge and attitudes towards anemia prevention in young women. This research is quasi-experimental research with the One Group Pretest-Posttest design. The sampling technique is probability sampling with random sampling. The sample size in this study was 69 adolescents at SMKN 4 Palangka Raya City and the statistical test used was the Wilcoxon test. The results showed that there was an effect of TikTok videos on the knowledge (P= 0.000) and attitudes (P=0.000) of adolescents. This study concludes that TikTok video media is quite effective in increasing the knowledge and attitudes of adolescents about anemia prevention, therefore providing education about anemia prevention can use TikTok video media as an alternative media in providing information to the public.